Do reported effects of acute aerobic exercise on subsequent higher cognitive performances remain if tested against an instructed self-myofascial release training control group?: a randomized controlled trial - Oberste-Frielinghaus, Max; Zimmer, Philipp (PLOS ONE, 2016)
A substantial body of evidence suggests positive effects of acute aerobic exercise (AAE) on subsequent higher cognitive functions in healthy young adults. These effects are widely understood as a result of the ongoing physiological adaptation processes induced by the preceding AAE. However, designs of published studies do not control for placebo, Hawthorne and subject expectancy effects. Therefore, these studies do not, at a high degree of validity, allow attributing effects of AEE on subsequent cognitive performance to exercise induced physical arousal. In the present study, we applied a randomized controlled blinded experiment to provide robust evidence for a physiological basis of exercise induced cognitive facilitation. Beyond that, the dose response relationship between AAE`s intensity and subsequent cognitive performances as well as a potentially mediating role of peripheral lactate in AAE induced cognitive facilitation was investigated. The 121 healthy young subjects who participated in this study were assigned randomly into 3 exercise groups and a self-myofascial release training control group. Exercise groups comprised a low, moderate and high intensity condition in which participants cycled on an ergometer at a heart rate corresponding to 45-50%, 65-70% and 85-90% of their individual maximum heart rate, respectively, for 35 minutes. Participants assigned to the control group completed a 35 minute instructed self-massage intervention using a foam roll. Before and after treatment, participants completed computer based versions of the Stroop task and the Trail Making Test as well as a free recall task. None of the applied exercise regimes exerted a significant effect on participants`performance at any of the applied cognitive testing procedure if compared to self-myofascial release training control group. Post hoc power analyses revealed no effect in the population of f = .2 or larger at a risk of type II error (β) ≤.183 for all measured variables. Our results, therefore, indicate that AAE induced cognitive facilitation is not (exclusively) based on physiological effects. Even if there is a substantial contribution of physiological adaptations to AAE in reported AAE induced cognitive facilitation, in this study, peripheral lactate could not be confirmed as such a factor. Peripheral lactate concentrations and cognitive testing performances after exercise showed rather small empirical and no significant associations. Our results suggest that other psychosocial aspects like expectations and social attention play an important role in AAE induced cognitive facilitation.
Gesehen am 07.09.2016